2020
DOI: 10.1002/ejhf.1989
|View full text |Cite
|
Sign up to set email alerts
|

Survival following a concomitant aortic valve procedure during left ventricular assist device surgery: an ISHLT Mechanically Assisted Circulatory Support (IMACS) Registry analysis

Abstract: The aim of this study was to compare early-and late-term survival and causes of death between patients with and without a concomitant aortic valve (AoV) procedure during continuous-flow left ventricular assist device (LVAD) surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Recently in this Journal Anker et al published the trial design and baseline characteristics of the EMPEROR-Preserved trial. 1,2 Compared to previous heart failure with preserved ejection fraction (HFpEF) trials investigating established drugs for the treatment of heart failure with reduced ejection fraction (HFrEF), the mechanistic evidence of empagliflozin as a rationale for treating patients with HFpEF seems to be more promising. Accordingly, we believe that the first experimental findings in human HFrEF and HFpEF myocardium have to be taken into consideration in this elegant clinical trial as they pave the way for a deeper mechanistic understanding of the potential effects of empagliflozin in the EMPEROR-Preserved trial.…”
Section: A Mechanistic Rationale For the Investigation Of Sodium-glucose Co-transporter 2 Inhibitors In Heart Failure With Preserved Ejecmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently in this Journal Anker et al published the trial design and baseline characteristics of the EMPEROR-Preserved trial. 1,2 Compared to previous heart failure with preserved ejection fraction (HFpEF) trials investigating established drugs for the treatment of heart failure with reduced ejection fraction (HFrEF), the mechanistic evidence of empagliflozin as a rationale for treating patients with HFpEF seems to be more promising. Accordingly, we believe that the first experimental findings in human HFrEF and HFpEF myocardium have to be taken into consideration in this elegant clinical trial as they pave the way for a deeper mechanistic understanding of the potential effects of empagliflozin in the EMPEROR-Preserved trial.…”
Section: A Mechanistic Rationale For the Investigation Of Sodium-glucose Co-transporter 2 Inhibitors In Heart Failure With Preserved Ejecmentioning
confidence: 99%
“…We read with interest the letter from the colleagues Loardi and Zanobini and would like to thank them for their useful comments on our recently published paper on the effects of concomitant aortic valve (AoV) procedures during left ventricular assist device (LVAD) implantation in patients enrolled in the ISHLT Mechanically Assisted Circulatory Support (IMACS) Registry. 1 The negative haemodynamic effects of untreated moderate-to-severe aortic regurgitation (AR) could be severe, while less severe AR might be less cumbersome. 2 Our results clearly demonstrated that a concomitant AoV procedure was an independent risk predictor for all-cause mortality post-LVAD implantation.…”
Section: Reply To 'Aortic Valve Surgery and Left Ventricular Assist Device: Lights And Shadows'mentioning
confidence: 99%
“…We read with interest the letter from the colleagues Loardi and Zanobini and would like to thank them for their useful comments on our recently published paper on the effects of concomitant aortic valve (AoV) procedures during left ventricular assist device (LVAD) implantation in patients enrolled in the ISHLT Mechanically Assisted Circulatory Support (IMACS) Registry. 1 The negative haemodynamic effects of untreated moderate-to-severe aortic regurgitation (AR) could be severe, while less severe AR might be less cumbersome. 2 Our results clearly demonstrated that a concomitant AoV procedure was an independent risk predictor for all-cause mortality post-LVAD implantation.…”
Section: Reply To 'Aortic Valve Surgery and Left Ventricular Assist Device: Lights And Shadows'mentioning
confidence: 99%
“…In the current issue of the Journal, Veenis et al 8 . used data from the International Society of Heart and Lung Transplantation Mechanically Assisted Circulatory Support (IMACS) registry to analyse how AR and aortic valve interventions affected outcome in 15 267 recipients of a primary continuous‐flow LVAD.…”
Section: Figurementioning
confidence: 99%